Sexual Violence and Nonconsensual Experiences Among Alt-Sex Communities’ Members - Wright, Susan (Journal of interpersonal violence, 2022)
BackgroundAs behaviors, alternative sexual (alt-sex) (i.e., kink, bondage, discipline, dominance, submission, sadism, and masochism , consensual non-monogamy, swinging, leather, and fetish practices) practitioners often emphasize that consent and boundaries are key elements of alt-sex activities. Despite these emphases, individuals experience consent violations and sexual assault both prior to engaging and during their involvement in alt-sex activities.PurposeThis study examines alt-sex practitioners? sexual assault and nonconsensual experiences in order to highlight potential means of intervention and prevention, as well as inform clinical and legal professionals.MethodsIn collaboration with the National Coalition for Sexual Freedom, this study uses an international survey of adults in alt-sex communities (N = 2996) to examine sexual assault and nonconsensual experiences both within and outside of alt-sex contexts.ResultsWe found a lower rate of consent violations in the alt-sex community (26%) compared to sexual assault as an adult outside of alt-sex contexts (34%) and sexual assault as a minor (40%). We found significant differences by groups in sexual assault as a minor (gender, sexual orientation, age, and live in the US or not), sexual assault outside of alt-sex contexts (gender, sexual orientation, and age), nonconsensual experiences in alt-sex contexts (gender, sexual orientation, age, and race), receiving nonconsensual touch in alt-sex contexts (gender, sexual orientation, and age), giving nonconsensual touch in alt-sex contexts (sexual orientation, age, living in the US or not, and race), and being falsely accused of nonconsensual touching in alt-sex contexts (gender, age, and living in the US or not). Within the most recent consent violation, the most common behaviors were non-kink related, except for lack of aftercare. Nearly 40% of participants reported the reasons for their most recent consent violation in alt-sex contexts were being selfish or caught up in the moment.ImplicationsFocused interventions are needed to address how different populations are experiencing assault and violations in alt-sex contexts.